Post-Global Aesthetics 21st Century Latin American Literatures and Cultures - Müller, Gesine; Loy, Benjamin (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo, 2022)
Phenomena such as the Covid-19 pandemic, climate change, or the surge of political populism show that the current phase of accelerated globalization is over. New concepts are needed in order to respond to this exhaustion of the global project: the volume scrutinizes these responses in the aesthetic realm and under a "post-global" banner, while incorporating alternative, non-Western epistemologies and literatures of the post-colonial Global South.